Gender differences in financial well-being among Malaysian college students - Falahati, Leila (2011)
Gender issues receive a considerable attention in financial behavior and financial well-being studies. The expansion of educational services in Malaysia resulted in the fast growing number of students enrolled in higher education. Education attainment has been known as the main factor to achieve higher level of financial well-being in later life, and evidence is growing showing that male and female college students have the different level of financial behavior and consequently, perceived different level of financial well-being. However, not much research done on financial wellbeing and financial behavior of university students in Malaysia. Financial behavior known as an important predictor of financial well-being and it is associated with several factors such as financial knowledge, financial attitude and financial socialization. Understanding the determining factors related to the financial well-being among male and female college students as the future labor force participates is crucial to further develop appropriate strategies in the educational system to promote better students' financial behavior. From gender perspective, social learning theory, family resource management theory and feminist economic theory could provide a valid basis for explaining and predicting gender differences in financial well-being among college students. This study sets out to examine the factors predicting financial well-being among male and female Malaysian college students. Research instrument has verified adequate levels of internal consistency, reliability, and content validity according to the past researches. Data of the research was collected through a self-administered questionnaire at 11 Malaysian universities (five publics and six privates) with a total number of 2,340 respondents. Descriptive analysis, t-test, Path analysis and Mediation analysis with Macro SPSS were employed to achieve the objectives of the study. Results of the study revealed that female students have higher level of financial wellbeing, effective financial behavior, lower level of financial knowledge, have more conservative financial attitude and financially socialized at later age compare to male students. Moreover, findings indicated that among several predictors, spendthrift attitude has the highest effect on financial well-being among male and female students. Results also indicated that financial socialization has an effect on the financial behavior and financial problem among male students but among female students, it has effect on financial behavior only. In addition, results indicated the mediation effect of financial behavior and financial problem on the relationship between predictors and financial well-being among male and female students. Among male students the following were factors that predict financial well-being: spendthrift attitude, secondary socialization agents, financial behavior, primary socialization agents, financial problem, financial socialization, conservative attitude and financial knowledge. Male students' financial behavior has full mediate effect in the relationship between financial socialization and financial well-being. Financial problem and financial behavior have partial mediate effect on the relationship between spendthrift attitude and secondary socialization agents; however, this effect was greater through financial behavior. On the other hand, among female students ranking by spendthrift attitude, primary socialization agents, financial problem, financial behavior, secondary socialization agents and conservative attitude were contributing to predict financial well-being. Female students' financial socialization by full mediate effect, it shows that financial behavior has effect on financial well-being. Financial problem and financial behavior have partial mediate effect on the relationship between spendthrift attitude and secondary socialization agents with financial well-being; however, this effect was greater through financial problem. Findings of research highlight the need for financial education for male and female students to be directed at assisting changes in financial attitude and financial behavior. Regarding to the strong influence of socialization agents, implications for further research and parents' education practices were discussed.